MODEL ASSET PRICING YANG BERLAKU DI INDONESIA: STUDY KASUS SAHAM UNGGULAN - Yunan Surono (Universitas Batanghari, 2018)
This study tested the influential factors in the estimation of stock return and compare the three models of asset pricing, i.e., Capital Asset Pricing Model, Three Factors Pricing models, and Four Factors Pricing Model. The purpose of this research is to obtain a model of asset pricing can provide estimated stock return with better among three types of models. The research sample is stocks LQ45 in Indonesia stock exchange (idx) during the period of 2005-2016. Regression analysis performed on variables, excess return market, size, book to market, and momentum is against the return of the monthly stocks fit each model to know the influence of variables and the feasibility of the model with the adjusted R square. Different test ANOVA is performed to obtain the standard deviation of each model and difference significance between the three models. The results showed: (1) factors in excess of market return, size premium, value premium, and momentum factors effect on stock return, (2) based on independent variables constituting influence, CAPM, Three Factors Pricing models or Four Factors Pricing Model can capture the behavior of stock prices on issuers who are members of group LQ45 on Indonesia stock market, (3) based on the adjusted R Square and standard deviation, Three Factors Pricing Model better than the CAPM and the Four Factors Pricing Model better than Three Factors Pricing Model, but all three models have a weak explanatory power as well as the results of significance of difference test that is not significant, so that the benefits of these models to estimated return expectations of stock market Indonesia is still questionable.